B-Cell Activating Factor (BAFF) in Systemic Lupus Erythematosus, Rheumatoid Arthritis, and Behçet’s Disease - Amina Badr ELDIN; Safaa SAYED; Gehan HEGAZY; Olfat SHAKER4 (Archives of Rheumatology, 2012)
Objectives: This study aims to determine B-cell activating factor (BAFF) serum levels in rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Behçet’s disease (BD) and correlate these levels with disease activity and severity. Patients and methods: Between December 2010 and December 2011, 63 Egyptian patients with collagen diseases [RA (n=21), SLE (n=21); BD (n=21)] were recruited from Cairo and Ain Shams University Hospitals, along with 21 apparently healthy individuals as controls. All participants underwent history taking, clinical examination, laboratory and radiological investigations, and disease activity score estimation. The serum BAFF level was measured by an enzyme-linked immunosorbent assay (ELISA) kit. Results: The BAFF serum levels were significantly elevated in patients with SLE and BD versus the healthy controls (p<0.011, p<0.023) and in SLE versus RA and BD (p<0.024, p<0.026). A significant positive correlation was found between the BAFF and C-reactive protein (CRP) (r=0.928, p<0.0001), the Disease Activity Score 28 (DAS28) (r=0.810, p<0.0001), and disease control (r=0.834, p<0.0001) in RA. Also, a significant positive correlation was found between BAFF and SLE Disease Activity Index (SLEDAI) score classification (r=0.894, p<0.0001) and SLEDAI score (r=0.748, p<0.0001) in SLE as well as between the BAFF and disease duration (r=0.578, p<0.006) in BD. Conclusion: The BAFF serum levels are increased in patients with SLE and BD versus the controls and in patients with SLE compared with those with RA and BD. They also have a positive correlation with disease severity in SLE and RA, which suggests that BAFF may play a role in the pathogenesis and activity of these diseases. These results may pose the possibility that a human monoclonal antibody drug which selectively inhibits BAFF biological activity may be useful in the treatment of active resistant cases.